Stress distribution in implant supported mandibular ovedentures and surrounding bone using three different types of attachments – a 3D finite element analysis - Vikram R Dulala; Lahoti Anurag; Puralasetty Srinivasa Rao; Kummari Subash Chander; Aditi C Sabnis; Asha O Reddy (Journal of Dr. NTR University of Health Sciences, 2019)
Background: Since mandibular complete denture faces problems with retention, stability, support mandibular implant supported overdenture is a more successful and durable treatment option. Different types of attachments used with mandibular overdentures improve the retention and dissipate stress as well. It is of paramount importance for the success of the prosthesis. Finite element analysis (FEA) is a very precise method for stress assessment in the bone. Materials and Methods: Mandibular 2 implant supported overdenture was considered. Noble Biocare replace implant of diameter 4.3 mm, length 11.5 mm was used in the study. 3 models were considered: Model A – Implant overdenture with Ball/O-ring attachment, Model B – Implant overdenture with Locator Attachment, Model C – Implant overdenture with Ceka attachment. A detailed, precise 3D solid model of human mandible was obtained upon which FEA could be optimized using Autodesk NETFABB ver. 8.1, a software and MAYA 3D software tool. These models were subjected to vertical, oblique and horizontal forces of 35N, 70N and 10N, respectively. Stress was assessed at different sites namely silicon cap/ring, abutment, implant–abutment interface, implant body, surrounding bone. The amount of force required to uplift the dentures was assessed. Results and Conclusion: Results showed that locator attachment showed least amount of stress generation under all three types of loads. Within the limitations of the study, it was concluded that locator attachment was better in terms of stress generation in comparison to Ball and Ceka attachment. It was the most retentive attachment in comparison to the other two attachments.